(untitled) (Bangladesh Journal of Animal Science, 2016)
The present research was conducted to investigate the effect of sex and age of goats on live weight, hot carcass weight, dressing percentage, chemical composition and pH of meat obtained from Black Bengal goat. Fifty goats of different age (up to 3 years) and sex groups (buck, castrated male, doe and kids) were slaughtered. After pre-slaughter weighing goats were sacrificed using the approved Halal method. The average live weight of doe up to one, two and three years of age were 12.51, 14.35 and 16.35 kg and of buck were 10.57, 19.29 and 37.05 kg, respectively. There were significant differences between the live weight of doe and buck at different age group. Hot carcass weight of doe and buck differ significantly among the different age group also differ significantly between the different sex groups goat. The mean hot carcass weight of castrated male at one year of age was 7.82 kg and was observed highest in castrated male than doe and buck. The average dressing percentage of doe, buck and castrated male at one year of age was 42.02, 39.01 and 43.56%, respectively but the values did not differ significantly. There were no significant differences of DM, moisture and CP content between doe and buck at different age group but significant differences were observed among the different age group of doe and buck. Fat content was significantly different among the different age group of doe and buck. There was significant difference of ash among the different age group of doe and buck. The pH values of goat meat did not differ significantly among the different age and sex of goats. From this study, it was concluded that the meat quantity in terms of hot carcass weight and dressing percentage were higher when castrated male slaughter within one year whereas maximum hot carcass weight was obtained when buck slaughter at the age 2-3 years and meat quality in terms of crude protein content was higher in meat obtained from buck and ether extract content was lower in buck meat when slaughter within one year. Bang. J. Anim. Sci. 2016. 45 (1): 19-24